Layer-by-layer coated hybrid nanoparticles with pH-sensitivity for drug delivery to treat acute lung infection - Ji Luo; Xiaobo Li; Siyuan Dong; Peiyao Zhu; Wenke Liu; Shuguang Zhang; Jiang Du (Taylor & Francis Group, 2021)
Bacteria-induced acute lung infection (ALI) is a severe burden to human health, which could cause acute respiratory distress syndrome (ARDS) and kill the patient rapidly. Therefore, it is of great significance to develop effective nanomedicine and therapeutic approach to eliminate the invading bacteria in the lung and manage ALI. In this study, we design a layer-by-layer (LbL) liposome-polymer hybrid nanoparticle (HNP) with a pH-triggered drug release profile to deliver antibiotics for the eradication of bacteria to treat ALI. The liposome is prepared by the lipid film hydration method with a homogenous hydrodynamic diameter and low polydispersity index (PDI). The antibiotic spectinomycin is efficiently loaded into the liposomal core through the pH-gradient method. The pH-sensitive polycationic polymer poly(β-amino ester) (PBAE) and polyanionic sodium alginate (NaAIg) layers are decorated on the surface of liposome in sequence via electrostatic interaction, resulting in spectinomycin-loaded layer-by-layer hybrid nanoparticles (denoted as Spe@HNPs) which have reasonable particle size, high stability, prolonged circulation time, and pH-triggered drug release profile. The in vitro results demonstrate that Spe@HNPs can efficiently induce the death of bacteria with low minimum inhibitory concentration (MIC) against Staphylococcus aureus (S. aureus) and drug-resistant MRSA BAA40 strains. The in vivo results reveal that Spe@HNPs can eradicate the invading MRSA BAA40 with improved antimicrobial efficacy and low side-effect for ALI treatment. This study not only reports a promising nanomedicine but also provides an effective method to prepare nanoplatforms for drug delivery and controlled release.